2018
DOI: 10.1111/acem.13650
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Placebo‐controlled Trial of Droperidol and Ondansetron for Adult Emergency Department Patients With Nausea

Abstract: Objective: The objective was to separately compare effectiveness of 1.25 mg of intravenous (IV) droperidol and 8 mg of IV ondansetron with 0.9% saline placebo for adult emergency department (ED) patients with nausea. A novel primary outcome measure, expected to aid clinical interpretation of reported results, was employed.Methods: A randomized controlled trial was conducted at the three EDs of Monash Health, Melbourne, Australia. The design was to demonstrate superiority of the active drugs over placebo. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 25 publications
2
19
2
Order By: Relevance
“…The provision of symptomatic treatment in the pre-hospital environment is an essential aspect of patient care. Although analgesia provision is common and evidence-based (26) , the role of antiemetics for treating nausea via the intravenous route is not as well de ned (27) . We found that pre-hospital PIVCs were most frequently used for analgesia and treating nausea.…”
Section: Discussionmentioning
confidence: 99%
“…The provision of symptomatic treatment in the pre-hospital environment is an essential aspect of patient care. Although analgesia provision is common and evidence-based (26) , the role of antiemetics for treating nausea via the intravenous route is not as well de ned (27) . We found that pre-hospital PIVCs were most frequently used for analgesia and treating nausea.…”
Section: Discussionmentioning
confidence: 99%
“…8 Eventually, the FDA conceded that the black box warning did not apply for doses of droperidol less than 2.5 mg. 9 Since that time, droperidol use has been studied in thousands of ED cases without any occurrence of fatal dysrhythmias, with dosing in many cases more than 10 mg. 10,11 Multiple trials published since the black box warning confirm the safety and potential superiority of low-dose droperidol for the treatment of nausea and vomiting in the ED. 12 A study of ED patients presenting with nausea showed that droperidol (1.25 mg given intravenously) reduced symptoms better than metoclopramide or prochlorperazine (change in nausea on 100 mm visual analog scale: -54.5 mm, -40.2 mm, and -40.5 mm, respectively), with the only adverse effect being selfreported restlessness or anxiety at 24-hour follow-up (71%, 25%, and 35%, respectively), with more than 90% satisfaction regardless of group. 13 Another study indicated less emesis when compared to ondansetron in the first 2 hours postoperatively.…”
Section: Use Of Droperidol In the Emergency Departmentmentioning
confidence: 99%
“…Although underpowered, the study reported that patients who subjectively "achieved the desired effect" were statistically higher in the droperidol group than in the placebo group (77% and 59%, respectively; absolute risk reduction, 18%; 95% confidence interval, 3% to 33%; number needed to treat, 5) and required less rescue medication. 12 In a recent Cochrane review, the only antiemetic to show a significant decrease in nausea was droperidol. 15 Droperidol has been used for many years for the safe treatment of headaches in the ED.…”
Section: Use Of Droperidol In the Emergency Departmentmentioning
confidence: 99%
“…An example of such a limitation is that because QT monitoring, such as with serial rhythm strips, was not done prospectively, it is possible that events of QT prolongation or even dysrhythmias were missed. Furthermore, we were unable to assess the relative frequency of complications compared to other therapies commonly substituted for droperidol in its absence 2,14,45,46 because of lack of a comparative group.…”
Section: Limitationsmentioning
confidence: 99%
“…Droperidol is a butyrophenone first-generation antipsychotic approved by the United States Food and Drug Administration (FDA) for the treatment of postoperative nausea and vomiting (PONV). 1 Over the past 30 years it has also become a cornerstone therapy for nausea and vomiting, 2 headache, 3 , 4 and agitation 5 7 in the emergency department (ED). 8 On December 4, 2001, the FDA issued a boxed warning (commonly called a “black box warning”) for droperidol, noting an association with QT prolongation and torsades des pointes (TdP), that recommended electrocardiogram (ECG) monitoring before and continued for 2–3 hours after droperidol administration, and that if QT prolongation (> 440 milliseconds [ms] for men, 450 ms for women) was present, droperidol not be administered.…”
Section: Introductionmentioning
confidence: 99%